Insane Colony - Valdizán, Hermilio (1918)
Some chroniclers, that not all of the kind referred to in his interesting book pages, curious accidents nervous nature, wonderfully healed. Among these cases, the referrals Writers, some have to invite the reader to consider how various syndromes of hysteria and there are others that take our thoughts to epilepsy.